Tuneable ionic control of polymeric films for inkjet based 3D printing - Karjalainen, Erno; Wales, Dominic J.; Gunasekera, Deshani H.A.T; Dupont, Jairton; Licence, Peter; Wildman, Ricky D.; Sans, Victor (American Chemical Society, 2018)
Inkjet printing is a powerful additive manufacturing (AM) technique to generate advanced and complex geometries. However, requirements of low viscosity and surface tension are limiting the range of functional inks available, thus hindering the development of novel applications and devices. Here, we report a method to synthesise materials derived from highly viscous or even solid monomers in a simple, flexible fashion and with the potential to be integrated in the printing process. Polymerisable ionic liquids (PILs) have been employed as a proof of principle due to the broad range of properties available upon fine tuning of the anion/cation pair and the high viscosity of the monomers. The method consists of the deposition and polymerization of a PIL precursor, followed sequentially by quaternisation and anion metathesis of the films. The fine control over the mechanical and superficial properties of inkjet printable polymeric films of neutral and cationic nature by post-polymerization reactions is demonstrated for the first time. A family of different polycationic materials has been generated by modification of cross-linked copolymers of butyl acrylate and vinyl imidazole with liquid solutions of functional reagents. The variation in the mechanical, thermal and surface properties of the films demonstrates the success of this approach. The same concept has been applied to a modified formulation, designed for optimal inkjet printing. This work will pave the way for a broad range of applications of inkjet printing, with a plethora of anion-cation combinations characteristic of PILs, thus enormously broadening the range of applications available in additive manufacturing.